Remarkable Improvement in the Mechanical Properties and CO2 Uptake of MOFs Brought About by Covalent Linking to Graphene. Issue 27 (10th June 2016) - Kumar, Ram; Raut, Devaraj; Ramamurty, Upadrasta; Rao, C. N. R.
Abstract: Metal–organic frameworks (MOFs) are exceptional as gas adsorbents but their mechanical properties are poor. We present a successful strategy to improve the mechanical properties along with gas adsorption characteristics, wherein graphene (Gr) is covalently bonded with M/DOBDC (M=Mg 2+, Ni 2+, or Co 2+, DOBDC=2, 5‐dioxido‐1, 4‐benzene dicarboxylate) MOFs. The surface area of the graphene–MOF composites increases up to 200–300 m 2  g −1 whereas the CO2 uptake increases by ca. 3–5 wt % at 0.15 atm and by 6–10 wt % at 1 atm. What is significant is that the composites exhibit improved mechanical properties. In the case of Mg/DOBDC, a three‐fold increase in both the elastic modulus and hardness with 5 wt % graphene reinforcement is observed. Improvement in both the mechanical properties and gas adsorption characteristics of porous MOFs on linking them to graphene is a novel observation and suggests a new avenue for the design and synthesis of porous materials. Abstract : A blend of strength : Reinforcing a metal–organic framework (MOF) matrix with graphene significantly enhances its mechanical properties and CO2 uptake. This strategy of strengthening a mechanically labile MOF matrix with graphene does not perturb the MOF's intrinsic microporosity.